A2ML1 and otitis media: novel variants, differential expression, and relevant pathways. Issue 8 (21st May 2019) - Larson, Eric D.; Magno, Jose Pedrito M.; Steritz, Matthew J.; Llanes, Erasmo Gonzalo d.V.; Cardwell, Jonathan; Pedro, Melquiadesa; Roberts, Tori Bootpetch; Einarsdottir, Elisabet; Rosanes, Rose Anne Q.; Greenlee, Christopher; Santos, Rachel Ann P.; Yousaf, Ayesha; et al.
Abstract: A genetic basis for otitis media is established, however, the role of rare variants in disease etiology is largely unknown. Previously a duplication variant within A2ML1 was identified as a significant risk factor for otitis media in an indigenous Filipino population and in US children. In this report exome and Sanger sequencing was performed using DNA samples from the indigenous Filipino population, Filipino cochlear implantees, US probands, Finnish, and Pakistani families with otitis media. Sixteen novel, damaging A2ML1 variants identified in otitis media patients were rare or low‐frequency in population‐matched controls. In the indigenous population, both gingivitis and A2ML1 variants including the known duplication variant and the novel splice variant c.4061 + 1 G>C were independently associated with otitis media. Sequencing of salivary RNA samples from indigenous Filipinos demonstrated lower A2ML1 expression according to the carriage of A2ML1 variants. Sequencing of additional salivary RNA samples from US patients with otitis media revealed differentially expressed genes that are highly correlated with A2ML1 expression levels. In particular,   RND3 is upregulated in both A2ML1 variant carriers and high‐ A2ML1 expressors. These findings support a role for A2ML1 in keratinocyte differentiation within the middle ear as part of otitis media pathology and the potential application of ROCK inhibition in otitis media. Abstract : In this report novel rare or low‐frequency variants were identified in multiple populations, including a novel splice variant c.4061 + 1 G>C that, together with gingivitis and a known A2ML1 duplication variant, confer increased susceptibility to otitis media in an indigenous Filipino population. RNA‐sequencing revealed that pathogenic A2ML1 variants decrease A2ML1 transcript levels, while changes in A2ML1 levels in otitis media patients result in differential expression of multiple genes that are known to be involved in mucosal, epithelial or infectious traits. Our findings support a role for A2ML1 in keratinocyte differentiation within the middle ear as part of otitis media pathology and the potential application of ROCK inhibition in otitis media.